Multi-Robot Learning with Bat Algorithm With Mutation (Bam) - Chandrathevan, Sathiamurthy (2022)
The mobile robotics is an active area of research. Several methods are under study to increase and optimize the working capabilities of multi robotic systems. These multi robotic systems or robot swarms have vast applications in industry as a human assistant to carry goods and can-do variety of jobs. Multiple techniques like swarm optimization, cuckoo algorithm and other such algorithms are under study for multi robotic systems. In this research, a biological bat inspired algorithm is implemented to achieve the target. BAT algorithm is implemented to achieve the target. BAT algorithm uses echolocation technique like bats to generate bat population and random data is generated, the robot then traverses and the distance is calculated which is compared to the distance from the obstacle. The loop continues and robot keeps moving. For more than one robot, robots have statistic as well as dynamic obstacles. So, the traversal speed and efficiency of bad algorithm reduces slightly.